P-118 How people die matters!. (1st September 2015) - Cairney, H; Hunter, P
Abstract : Background: It has been widely acknowledged across Australia that current practices in end-of-life (EOL) care require change to ensure that safe, high quality care is delivered at the EOL. Across Alfred Health it was identified that whilst a number of pieces of work addressing EOL care were underway, they were not always linked or coordinated. A strategic approach to EOL care was required. Aim: To develop an Alfred Health approach to providing high-quality treatment and care to support patients who are approaching the end of their life, to live as well as possible until they die, and to die with dignity. Methods: A collaborative learning approach was taken to improving EOL care across Alfred Health. An interdisciplinary EOL working group was established including consumer representation and strong support from senior leadership across the organisation. An EOL care framework and set of key principles were agreed upon and action areas developed. Results: Improvement initiatives included; Development of several EOL care related guidelines EOL communication skills training Processes for dealing with disagreement around EOL decisions Development of ICU admission exclusion criteria Further embedding of advance care planning in clinical areas Discussion: Leadership at all levels of the organisation has been essential for improving EOL care across Alfred Health. Executive and clinical endorsement and support was required in the development of a framework and key principles for EOL care. Patient and clinician stories were important in establishing an innovative approach including the development of a supportive culture and governance for EOL care.